Influence of WS2 content on high temperature wear performance of magnetron sputtered TiN-WSx thin films. Issue 16 (November 2019) - Serra, E.C.; Soares, V.F.D.; Fernandez, D.A.R.; Hübler, R.; Juste, K.R.C.; Lima, C.L.; Tentardini, E.K.
Abstract: TiN-WSx thin films with varying WSx content were co-deposited by reactive magnetron sputtering. GAXRD analyses showed that the addition of 4 at.% WSx led to loss of crystallinity of TiN phase and a complete amorphous characteristic was manifested upon incorporation of 19 at.% WSx . Nanohardness results indicated that TiN-WSx containing 4 and 19 at.% WSx presented 19.7 GPa and 18.4 GPa, respectively, following the rule of mixtures. Friction coefficient and wear rates measured in reciprocated tribological tests revealed that TiN-WSx coatings present an improved tribological performance when compared to pure TiN thin film at room temperature, registering friction coefficient of 0.42 ± 0.05 and 0.19 ± 0.03 for samples with 4 and 19 at.% WSx, respectively. Wear tests at high temperatures evidenced that sample with 4 at.% WSx did not provide advanced protection to substrate at 343 K and above due to deterioration. On the other hand, coating with 19 at.% WSx maintained low friction coefficient up to 343 K, registering an optimum wear rate of 0.86 × 10 −17  m 2 /N with no cracking occurrence.